PENATALAKSANAAN FISIOTERAPI PADA KONDISI SPONDYLOSIS CERVICAL: STUDI KASUS - Maulida Wijaya Putri (Politeknik Unggulan Kalimantan, 2024)
Cervical spondylosis is a term that encompasses a variety of progressive degenerative changes that affect all components of the cervical spine (i.e. intervertebral discs, facet joints, Luschka joints, ligamentum flava, and lamina). This is a natural aging process and occurs in most people after the fifth decade of life.This type of research is a case study conducted at the Physiotherapy Polyclinic at Ulin Hospital, Banjarmasin. The research time will be in September 2023 in the Physiotherapy room at Ulin Hospital, Banjarmasin. The subject of this study was a 40 years old woman who experienced Cervical Spondylosis. The interventions used are MWD, US, Isometric Exercise, and Traction. The patient complained of stiffness and pain when moving the neck since January 2023 due to cervical spondylosis. Pain was felt when the neck is moved to the right, left, up and down. After physiotherapy and evaluation, the results showed a reduction in pain, a reduction in spasm and an increase in the patient's functional ability. Respondents with cervical spondylosis after being given interventions in the form of MWD, US, Isometric Exercise and Traction experienced a decrease in pain, spasm and an increase in the patient's functional ability.